Diagrams illustrating the sciences of astronomy and geography - Rock and Sons; Peacock and Mansfeld; Strand Ackermann and Co.; Reynolds, James; Reeves and Sons (James Reynolds, 1850)
Definition of terms used in astronomy and geography [okładka].
drawn a. engraved by John Emslie ; James Reynolds ; Strand Ackermann and Co. ; Reeves and Sons ; Rock and Co. ; Peacock and Mansfield ; T. Clark.
Keywords: Tektonika; wykresy; Świat; Niebo; Geografia; Pory roku; Gwiazdy; Jeziora; Meteorologia; Układ słoneczy; Teleskop; Zaćmienia; Kartografia; Geologia; Góry; Astronomia; Rzeki; Księżyc; w kartografii; Rosse zob. Lewiatan; Lewiatan - teleskop